Projected changes in the seasonality of rainfall and temperature over Southern Africa under low mitigation - Mfopa, Caroline Reitumetse (My University, 2022)
The single most prominent characteristic feature of southern African climate is its pronounced dry-wet seasonality, as opposed to the warm-cold seasonality that dominates climate of the high latitudes of the Northern Hemisphere. It is thought that the African savannahs, the dominant biome in southern and East Africa, evolved in the presence of fire and dry-wet seasonality over the last 10 million years. Global warming is already impacting on southern African climate, with the interior regions recording a rate of temperature increase almost twice the rate of global warming, over the last several decades. The main aim of this research was to investigate how regional climate change in southern Africa may impact on the seasonality of rainfall and temperature across the region, using the large ensemble of CMIP6 global climate model projections. Verification of the climate models revealed that they are capable to simulate intraannual variability (that is, the seasonal cycle) of both rainfall and temperature in southern Africa with remarkable realism. This holds true for regions with diversely different climatic regimes: the winter-rainfall region of South Africa, the larger summer rainfall region of southern Africa, and the bimodal rainfall region of East Africa. There is a single exception, namely the narrow all-year rainfall region of the Cape south coast of South Africa, where the correlation between the model simulations and observations in terms of intra-annual rainfall variability is substantially weaker than for other regions in southern Africa. The CMIP6 ensemble projects general reductions in rainfall over southern Africa under low mitigation, with corresponding drastic increases in temperature. These results confirm the 2018 classification by the IPCC SR1.5 report, of the southern African region being a climate change hotspot: when a warm and dry region becomes even warmer and likely also drier, the options for adaptation are limited. There are some important exceptions, in terms of the general pattern of change projected by the CMIP6 ensemble. The first is the northernmost parts of southern Africa, located in the tropical savannah zone, where increases in rainfall are projected. This pattern of change relates to the expansion of the humid tropical belt in a warmer climate. The second is the eastern escarpment areas of South Africa where increases in rainfall are similarly projected, driven by an increase in specifically summer rainfall. This implies iv an increase in the nature of rainfall – namely more intense rainfall events in summer and an increase in the amplitude of dry-wet seasonality. For most of the southern African region, however, general drying is projected, in conjunction with drastic warming. In fact, the CMIP6 ensemble projects staggeringly large temperature increases over the interior regions of southern Africa under low mitigation relative to 1979-2014. Over large regions of the interior, and across all seasons, this change is in the order of 5 °C by the end of the century. Such drastic increases in temperature, which translates to enhanced evaporation from soils, in combination with projected reductions in rainfall effectively suggests a longer burning season, and a shorter growing season (through reductions in soil moisture). The results point to the need for the region to focus strongly on climate change adaptation actions, in addition to its efforts on fairly contribute to greenhouse gas mitigation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Temperature over Southern Africa; Southern African climate; Seasonality of Rainfall